Increased Electroencephalographic High Frequencies during the Sleep Onset Period in Patients with Restless Legs Syndrome - Ferri, Raffaele (Associated Professional Sleep Societies, LLC, 2014)
STUDY OBJECTIVES: To analyze the electroencephalographic (EEG) spectral content in untreated patients with restless legs syndrome (RLS) during the sleep onset period (SOP) and during the quiet wakefulness preceding sleep, in order to test the hypothesis that a state of hyperarousal might be present during the SOP with RLS. SETTING: Sleep Research Centre. PATIENTS: Twenty-seven untreated consecutive patients with RLS (mean age = 53.6 y), 11 untreated consecutive patients with primary insomnia (mean age = 58.9 y), and 14 normal controls (mean age = 50.3 y). METHODS: SOP was defined as the 10-min period centered with the occurrence of the first sleep spindle in the EEG, and then subdivided into SOP-1 (period of 5 min before the first spindle) and SOP-2 (period of 5 min following). Leg movements occurring during SOP were counted and used as a covariate in the statistical analysis. Also, one period of 1 min of artifact-free quiet wakefulness after lights off was identified. EEG spectral analysis was run during these periods using the C3/A2 or C4/A1 channel. MEASUREMENTS AND RESULTS: Increased EEG alpha and beta bands and/or beta/delta ratio in RLS versus normal controls, during both wakefulness preceding sleep and SOP (both parts SOP-1 and SOP-2) were found, which were, however, smaller than the increases found in patients with insomnia. CONCLUSION: The results of this study support the hypothesis of the presence of a state of hyperarousal in restless legs syndrome (RLS) during the sleep onset period. Treatment for RLS might need to take these findings into consideration. CITATION: Ferri R, Cosentino FI, Manconi M, Rundo F, Bruni O, Zucconi M. Increased electroencephalographic high frequencies during the sleep onset period in patients with restless legs syndrome. SLEEP 2014;37(8):1375-1381.